Rankings of High School Sports Injury Rates Differ Based on Time Loss Assessments. Issue 6 (November 2017) - Kerr, Zachary Y.; Roos, Karen G.; Djoko, Aristarque; Dompier, Thomas P.; Marshall, Stephen W.
Abstract : Objective: To examine how injury definition inclusiveness affects the rank order of injury rates in 27 high school (HS) sports. Design: The National Athletic Treatment, Injury and Outcomes Network (NATION) used certified athletic trainers (ATs) to collect injury and athlete-exposure (AE) data in practices and competitions for 27 HS sports during the 2011/2012 to 2013/2014 academic years. Time loss (TL) injuries resulted in ≥24 hours of participation restriction. Nontime loss (NTL) injuries resulted in <24 hours of participation restriction. Setting: Aggregate injury and exposure data collected from 27 HS sports. Participants: High school student-athletes. Interventions: Sports injury data from the National Athletic Treatment, Injury and Outcomes Network. Main Outcome Measures: Time loss and TL + NTL injury rates were calculated. Sport-specific rates were placed in rank order, stratified by gender. Results: Most of the 47 014 injuries reported were NTL (82.8%). Among boys' sports, TL injury rates were greatest in football (3.27/1000AE) and wrestling (2.43/1000AE); TL + NTL injury rates were greatest also in football (15.29/1000AE) and wrestling (11.62/1000AE). Among girls' sports, TL injury rates were greatest in soccer (1.97/1000AE) and basketball (1.76/1000AE); TL + NTL injury rates were greatest in field hockey and lacrosse (both 11.32/1000AE). Conclusions: The rank order of injury rates and the resulting injury prevention priorities may depend on injury definition inclusiveness, particularly in female HS sports.